Organic thermoelectric generators: working principles, materials, and fabrication techniques - Eryilmaz, Ilknur Hatice; Chen, Yan-Fang; Mattana, Giorgio; Orgiu, Emanuele (Chemical communications (Cambridge, England), 2023)
Organic thermoelectricity is a blooming field of research that employs organic (semi)conductors to recycle waste heat through its partial conversion to electrical power. Such a conversion occurs by means of organic thermoelectric generator (OTEG) devices. The recent process on the synthesis of novel materials and on the understanding of doping mechanisms to increase conductivity has tremendously narrowed the gap between laboratory research and their application in actual applications. This Feature Article intends to highlight the impressive progress in materials and fabrication techniques for OTEGs made in recent years.